1996
DOI: 10.1136/jcp.49.7.549
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation indexes--a comparison between cutaneous basal and squamous cell carcinomas.

Abstract: Aims-To compare differences in cell proliferation indexes and apoptotic indexes between cutaneous basal and squamous cell carcinomas, in an attempt to suggest an explanation for the differences in their biological behaviour. Methods-Forty cases of cutaneous basal cell carcinoma (BCC) and 40 cases of moderately and well differentiated squamous cell carcinoma (SCC) were retrieved from the archives. Sections, 4 gm thick, were cut from formalin fixed, paraffin wax embedded tissue in each case and stained with haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
1
17
2
Order By: Relevance
“…At this stage, one finds proliferation of the subadjacent keratinocytes after migration has taken place. IFI27 was also strongly expressed in a subpopulation of SCC, unlike in BCC, which may reflect their histopathological differences and the higher proliferation index of SCC (al-Sader et al, 1996). IFI27 may therefore be a marker of certain epithelial cancers.…”
Section: Discussionmentioning
confidence: 96%
“…At this stage, one finds proliferation of the subadjacent keratinocytes after migration has taken place. IFI27 was also strongly expressed in a subpopulation of SCC, unlike in BCC, which may reflect their histopathological differences and the higher proliferation index of SCC (al-Sader et al, 1996). IFI27 may therefore be a marker of certain epithelial cancers.…”
Section: Discussionmentioning
confidence: 96%
“…We used several statistical approaches to analyze the data, exploring different exposure periods, and various casecontrol definitions within the cohort design. We also explored the possibility of separate associations for BCC and SCC, acknowledging the many indications that BCC and SCC are biologically distinct: essential differences in histogenesis, 46-49 molecular pathways 50,51 and vascularization patterns. 52,53 The major limitation of our study is the lack of data regarding the doses and duration of NSAID use in our subjects.…”
Section: Discussionmentioning
confidence: 99%
“…According to most studies published in the literature (Al-Sader et al 1996;Matsuta et al 1996;Horlock et al 1997; Tilli et al 2002;Mazzarelli et al 2003;Ionescu et al 2006;Correa et al 2009), mean BCC growth fraction detected immunohistochemically by antibodies against Ki-67 antigen ranged between 20-41%. In our study, the mean value of 27.4% is in agreement with the results of the above-mentioned papers.…”
Section: Discussionmentioning
confidence: 99%
“…This observation raises the possibility that it may have partly different impact on evolution and biological behavior of this neoplasia. Moreover, the vast majority of the authors (Baum et al 1993;Al-Sader et al 1996;Horlock et al 1997;Lee et al 2000;Tilli et al 2002;Mazzarelli et al 2003;Ionescu et al 2006) found that Ki-67 growth fraction varied considerably between different histomorphological BCC types, even in the tumors belonging to the same group. Our results have shown a wide percentage range in each histological BCC type as well, regardless whether they were primary or recurrent lesions.…”
Section: Discussionmentioning
confidence: 99%